2010
DOI: 10.14710/jitaa.35.4.251-256
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF COMBINATION OF YEAST (Saccharomyces cerevisae + Candida utilis) AND HERBS SUPPLEMENTATION IN FINISHING DIET ON CARCASS CHARACTERISTICS OF BEEF CATTLE

Abstract: A 75 days feeding trial was completed to study the effect of inclusion of a combined probiotic yeast+herbs in finishing diet on carcass characteristics of beef cattle. Thirty bull of Ongole crossbred, age 2.5-3 years old with average body weight (BW) of 320 kg were used in this experiment. They were divided into 2 groups, each of 15 animals and were allotted to control and treatment. They were slaughtered at around 450 kg BW. The treated animals were given a supplementation containing combined yeast (Saccharom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Similarly, the intestinal digestive physiology and metabolism of shrimp have been improved by the incorporation of C. butyricum in the diet (Duan et al, 2017). More recently, it has been shown that the combined effect of probiotics and herbal plants had significantly positive outcome than independent application in macrobrachium rosenbergii (Tadese et al, 2020), broiler chickens (Duskaev et al, 2018), swamp buffalo with improvement obtained on carcass characteristics (Mahyuddin & Widiawati, 2009) and humans with significantly reduced enteric pathogens (Shipradeep et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the intestinal digestive physiology and metabolism of shrimp have been improved by the incorporation of C. butyricum in the diet (Duan et al, 2017). More recently, it has been shown that the combined effect of probiotics and herbal plants had significantly positive outcome than independent application in macrobrachium rosenbergii (Tadese et al, 2020), broiler chickens (Duskaev et al, 2018), swamp buffalo with improvement obtained on carcass characteristics (Mahyuddin & Widiawati, 2009) and humans with significantly reduced enteric pathogens (Shipradeep et al, 2012).…”
Section: Introductionmentioning
confidence: 99%